Uso da celulose liofilizada em lesões de nervos periféricos com perda de substância - Luís Renato Mello; Yanara Feltrin; Rafael Selbach; Gilberto Macedo; Cléverton Spautz; Leandro José Haas (2001)
Lyophilized cellulose was analysed to verify the degree of inflammatory reaction and axon realignment in the sciatic nerve after loss of neural substance. Ten mongrel dogs were divided into: Group 1 - 1 cm section of sciatic nerve which was replaced at lesion site; Group 2 nerve section without fragment replacement. The section site was involved with lyophilized cellulose. Group 3 -1 cm fragment section sutured epineurally. Motor response started at eighth week. Moderate fibrotic reaction to cellulose was seen in Group 1 and 2 animals. Groups 1 and 3 showed coaptation between the nerve and nerve graft with ongoing axons. In Group 2, 1 dog showed regrowth of axons through the empty space. It was concluded that lyophilized cellulose caused moderate fibrous reaction when implanted in peripheral nerve lesions with loss of substance; it can act as envelop protection in those lesions mainly if a neural graft is inserted.